Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication